Conformational and docking studies of acyl homoserine lactones as a robust method to investigate bioactive conformations. (April 2019) - Soulère, Laurent; Queneau, Yves
Graphical abstract: To create your abstract, type over the instructions in the template box below. Fonts or abstract dimensions should not be changed or altered. Highlights: Exhaustive conformational search of diverse acyl Homoserine Lactones. Comparison of torsion angles with co-crystallized AHLs (X-Ray structure). Rigid docking of selected closest conformation(s) (Validation of the method: low RMSD). Application of the method (Conformation search/rigid docking) to AHLs with unknown co-crystallized structure. Abstract: A method aiming at investigating possible bioactive conformations of acyl homoserine lactone (AHL) quorum sensing (QS) modulators is established. The method relies on the exhaustive conformational analysis of AHLs by varying torsion angles around the amide group then on the selection of the closest conformation to those known from co-crystallized XRD data of AHL-receptor complexes. These latter are then docked as rigid ligand within the receptor binding site, leading to interactions with binding site residues which are highly consistent as compared with the data arising from XRD studies. The method is first validated using AHLs for which XRD data of their complexes with their cognate receptor are available, then extended to examples for which the binding mode is still unknown. Three compounds were used to validate the method: hexanoyl homoserine lactone (HHL) as an example of autoinducer, 3-oxo-butanoyl homoserine lactone (OBHL), as a representative model of 3-oxo-AHLs, and 4-(4-chlorophenoxy)butanoyl homoserine lactone (CPOBHL) as an example of a QS inhibitor. The conformational analysis of these three compounds to their cognate protein (TraR, SdiA, LasR and CviR) provides the data which enable the next rigid docking step. Further rigid docking of the closest conformations compared to the known bioactive ones within the binding sites allows to recover the expected binding mode with high precision (atomic RMSD < 2 Å). This "conformational analysis/torsion angle filter/rigid ligand docking" method was then used for investigating three non-natural AHL-type QS inhibitors without known co-crystallized XRD structures, namely was 2-hexenoyl homoserine lactone (HenHL), 3-oxo-4-phenylbutanoyl homoserine lactone (OPBHL) and 3-(4-bromophenyl)propanoyl homoserine lactone (BPPHL). Results provide insights into their possible binding mode by identifying specific interactions with some key residues within the receptor binding site, allowing discussion of their biological activity.